Media Konkret untuk Mengajarkan Bangun Datar - Unaenah, Een; Oktapiani, Rizka; Mufidah, Wiradatul (Lembaga Yasin AlSys, 2023)
Learning will continue to be tiring if educators generally organize learning and teaching exercises. So that in the end Students will experience boredom and lack of enthusiasm enthusiastic to imitate. This arrangement The purpose of this is to show that there is an increase in the learning outcomes of class VI students at SDN Buaran Bambu III Pakuhaji Region, after involving substantial media such as cardboard, wall clocks, three-sided rulers in mathematical illustrations related to the material. Substantial Media for Displaying Level Forms. Basic information acquired in this study expressed that out of 42 understudies, just 25 kids scored over 65 or expressed to have graduated, 17 children had not completed their exams, because the scores obtained were still below 65 in cycle I. The information obtained indicated that the expansion of learning outcomes. student. It was informed that out of 32 students, 27 children had graduated and 15 children had not finished studying. Based on these findings, the second cycle was carried out, Additionally, the outcomes show a huge expansion in understudies' comprehension: 84% of the assignments according to the research findings. Instructors ought to utilize learning media or instructing helps that are genuine on the grounds that they can be utilized as an elective wellspring of advancing by focusing on understudy exercises and custom fitted to their requirements their contents.